Investigation of H atom and free radical behaviour in clathrate hydrates of organic molecules. (March 2020) - Mozafari, Mina; Chandrasena, Lalangi; McKenzie, Iain; Samedov, Kerim; Percival, Paul W.
Abstract: Clathrate hydrates are icy materials composed of a lattice of water molecules containing well-defined cavities which can accommodate small guest molecules. Their large storage capacity makes clathrates attractive media for a variety of gas storage and separation applications, but there is relatively little information on the chemical stability and diffusion of guest molecules. At the fundamental level inter-cage transition energies have been calculated, but the results need to be tested with experimental data. Ideally this should involve single-atom transport, using an isotopic tracer or spin label. Muonium (Mu = μ + e – ) qualifies on both counts. As a single-electron atom with the muon as nucleus it may be considered a light isotope of hydrogen. Furthermore muonium and its reaction products may be monitored by muon spin spectroscopy. In recent years we have used this method to probe H-atom and free radical behaviour in clathrate hydrates. The current work extends studies to benzene and acetone clathrate hydrates. Of note is the simultaneous detection of muonium and muoniated radicals in the same sample. This can happen when Mu is trapped in an empty cavity, remote from its reaction partner. Increase in temperature leads to transport of Mu between cages and results in encounters with reactive guest molecules. By studying the temperature dependence of Mu and radical signals, we have been able to determine the activation energy for transport of Mu between cavities. Highlights: Positive muons stopped in clathrate hydrates form muonium (Mu), a light isotope of H. Mu reacts with unsaturated organic guest molecules to form caged radicals. At low temperatures muonium and muoniated radicals can be detected simultaneously. At higher temperatures Mu is mobile and reacts with molecules in nearby cavities.